RESEARCH OF THE STYLE OF PSYCHOLOGICAL AND PEDAGOGICAL INTERACTION BETWEEN THE SUBJECTS OF EDUCATIONAL SPACE - Slobodianyk, Natalia (PSYCHOLOGICAL JOURNAL, 2019)
In this article, the results of the empirical research of the style of psychological and pedagogical interaction between the participants of the educational space are analyzed. The psychological and pedagogical interaction is considered as a phenomenon having a dual nature and appearing on the interweaving of the processes of interaction between the individuality and environment that characterizes their direct interaction. It is underlined that in order to fully substantiate the phenomenon of psychological and pedagogical interaction, it is necessary to pay attention to its characteristic, such as style, which refers to individual typological means, methods and peculiarities of the socio-psychological interaction between a teacher and pupils. It is noted that the notion of "style" can be perceived in different meanings - both in a broad and narrow way. In a broad sense, it covers the peculiarities of all components of the activity, and in the narrow - only peculiarities of human behavior. An empirical study of the implementation of the style of psychological and pedagogical interaction by teachers during the classes provided an opportunity to determine the parameter of the teacher's attitude towards children. The connection between the style of psychological and pedagogical interaction and the modalities of the attitude of teachers towards children is revealed. Observation of the activities of the studied teachers and analysis of the protocols of psychological and pedagogical conversation allowed to add a description of the styles of psychological and pedagogical interaction: consistently positive, consistently negative, uncoordinated positive and negative, uncoordinated negative and positive, uncertain.